Nonamyloidotic Light Chain Cardiomyopathy: The Arrhythmogenic Magnetic Resonance Pattern. Issue 14 (5th April 2016) - De Lazzari, Manuel; Fedrigo, Marny; Migliore, Federico; Cianci, Andrea; Cacciavillani, Luisa; Tarantini, Giuseppe; Giorgi, Benedetta; Iliceto, Sabino; Thiene, Gaetano; Valente, Marialuisa; Angelini, Annalisa; Adami, Fausto; et al.
Abstract : Supplemental Digital Content is available in the text.